Teaching Staff’s and Students’ Initial Perceptions and Satisfaction With Teaching and Learning via the Blackboard LMS - Al-Malki, Norah; AbdulKarim, Abdul Halim; Shoie Alallah, Fouad (International Journal of Advanced Corporate Learning (iJAC), 2015)
The aim of this paper is to demonstrate the degree of teaching staff’s and Students’ satisfaction with the teaching and learning experience via the Blackboard â„¢ Learning Management System (LMS), recently acquired by King Abdulaziz University (KAU) as an online solution supporting distance education programs. Teaching staff’s and students’ perceptions about the e-courses offered via the LMS were collected in four areas: 1) E-course Content, 2) LMS Ease of Use and Performance, 3) Communication Facilitation, and 4) Delivery Methods. The respondents’ observations on these topics were gathered via two short, Likert-scale questionnaires which were distributed during the Summer Semester of 2014. The researchers sought, through this preliminary investigation, to identify issues which might impact the implementation of the Blackboard LMS in the Distance Education programs in KAU. Generally, the results indicate a relatively high satisfaction rating of the LMS from both groups of users.